Trajetória intelectual de José Américo: contribuições para o pensamento social brasileiro - Brandão, Nilvanda Dantas (2012)
The objective of this work is to interpret the performance of José Américo de Almeida from a sociological viewpoint, in a context which comprises the period between the years 1920 and 1960. This period was marked by the modernization of industry, political and artistic transformations, and the shaping of Brazilian social thought. We have sought to highlight aspects of the writer s intellectual trajectory which signify contributions to the Social Sciences, expressed both through his writings and actions in the literary, political and scientific fields. The discussion has originated in the dialogue struck up between the interpreters of the National in the process of the institutionalization of Social Sciences in Brazil, and the intellectual from Paraíba, and involves the analysis of his works, including scientific texts, novels, autobiography, speeches, interviews, memoirs and letters, dealing with themes related to a modern, democratic Brazil where there is a mixture of races. The conclusion was reached that the contribution of José Américo towards the shaping of Brazilian social thought , in the scientific field, lies in his proposal of an anthrosociology, which defends positivities (creativity, resistance and diversity)in the mixed-race national identity, and its disassociation from social and economic backwardness. The lack of development is understood by him as the effect of the lack of a democratization of power and capital. This inspired his disclosure and social criticism in the novels, which have become his innovative contribution to the literary field In the political field his contribution is his idea of democracy. The theoretical and methodological foundation on which the present work is based is the theory of reflexivity of Pierre Bourdieu, highlighting the concepts of Field and Habitus. This research belongs to the ambit of studies of intellectual trajectories, more specifically, in the field of Brazilian social thought.